1901 Utah Laws 76, ch. 77, § 1. - (:unkn) unknown (My University, 1901)
That every person who knowingly leave with or delivers to another, or to any express or railway company or other common carrier, or to any warehouse or storehouse any package containing nitro-glycerine, dynamite, guncotton, gunpowder, or other highly explosive compound, or any benzine [sic], gasoline, phosphorus, or other highly inflammable substance or any vitriol, . . . or other dangerous acid . . . to be handled, stored, shipped or transported, without plainly marking and indicating on such package the name and nature of the contents thereof, is guilty of a misdemeanor, and punishable by a fine not exceeding three hundred dollars, or by imprisonment in the county jail not exceeding six months.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER